Class Management in Islamic Cultural History Subject at Madrasah Tsanawiyah - Syahbana, Thulus G.; Rahmi, Elvi; Indria, Anita; Rahawarin, Yunus; Maradona, Maradona (Ahlussunnah: Journal of Islamic Education, 2022)
Class management is a determinant of creating a comfortable, conducive, and efficient learning atmosphere and learning objectives can be achieved. The aim of this research is to look at forms of classroom management that are conducive to  history of Islam subjects at madrasah tsanawiyah muhammadiyah Padang Panjang. This research uses qualitative descriptive methods and the technique of purposive sampling. To obtain data, researchers used observation, interviews, and documentation. The data processing techniques are data reduction, data presentation, conclusions, or verification. Researchers use these data processing techniques to obtain accurate research results. The research results obtained are; i) class management requires a warm and enthusiastic teacher attitude, creating challenges in the learning process so that students become enthusiastic, having the ability to vary and be flexible in teaching so that students are active and try to focus during the learning process, emphasizing positive things and cultivating self-discipline so that the learning process is not disturbed and students have a sense of responsibility. ii) skills in preventive classroom management in the form of: a). being responsive and paying attention can prevent disturbances from students, b). providing clear instructions can help students stay focused in the learning process. Then classroom management skills are repressive in the form of a) modifying behavior, which can make students quickly and easily understand the material because they do not commit deviant actions during the learning process, b) finding and solving problematic behavior, which can make the learning process comfortable, effective, conducive and efficient. iii) supporting factors for classroom management such as curriculum, buildings, and teachers. Inhibiting factors such as facilities and infrastructure, as well as students and families in classroom management, can be a reference in improving or reducing the atmosphere of the learning process. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.